Penerapan Modal Sosial dalam Pengembangan Kelompok Usaha Bersama Rumah Lengkepe Kreatif di Kecamatan Tuah Madani Kota Pekanbaru - Dia Meirina Suri; Tarmizi Yussa; Pahmi Amri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
One of the organizations engaged in empowerment is the Lengkepe Creative Joint Business Group consisting of homemakers who carry out activities to improve the family's economy. This KUB comprises various businesses such as food, handicraft, and medicinal plant cultivation. Businesses run by KUB members are still small businesses and have yet to provide an economic boost to members. This Joint Business Group was established to help homemakers earn money and increase family income. The problem faced by KUB is inadequate capital to produce and market products. This service was carried out to provide enlightenment on how to utilize the social capital around KUB to develop KUB. The method used in this service was comprehensive assistance for all KUB members to identify social capital that can be utilized in the development of KUB. The activity results showed that social capital could be utilized, namely online and offline networks, in product marketing and obtaining raw materials. The following assistance needed for the KUB is institutional support that provides legality to the products produced.